Pengaturan Pemberlakuan Pembatasan Kegiatan Masyarakat di Provinsi Bali Dalam Upaya Penanggulangan Penyebaran Covid 19 Menuju Bali Era Baru - Kadek Julia Mahadewi (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2023)
The purpose of this study is to examine the law enforcement of the Restriction of Community Activities in Bali Province in accordance with the National legal system. This study uses an empirical legal approach, with a descriptive nature of research. The regulation of limiting community activities based on the Regulation of the Governor of Bali Province No. 40 concerning the Application of Health Protocols is emphasized again in the Circular of the Governor of Bali Number 7 of 2021 concerning the Regulations for Restricting Community Activities shows that the implementation is not yet effective. The law in this society can be seen that there is still a high number of numbers exposed to Covid 19 so that the Government continues to introduce new regulations and extend the Regulations for Clearing Community Activities to reduce the rate of development of Covid 19.